Maritime Security and Drug Threats in the Border Waters of Bintan Regency: The Perspective of the Bintan Resort Police - Elyza Riani; Yossi Oktalina (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
Bintan Regency, located in Indonesia’s Riau Islands Province, occupies a strategic maritime position adjacent to Singapore and Malaysia, making it a vital yet vulnerable zone for transnational narcotics trafficking. The geographical characteristics of extensive coastlines, scattered small islands, and numerous unofficial ports provide opportunities for smugglers to exploit weak surveillance and limited enforcement capacity. This study aims to analyze the strategies, challenges, and institutional coordination of the Bintan Resort Police (Polres Bintan) in combating maritime-based narcotics smuggling. Using a qualitative descriptive method, data were collected through in-depth interviews, direct observation, and documentation studies, then analyzed using the Miles and Huberman model with triangulation for validation. The findings reveal that the Polres Bintan plays a crucial role in early detection and prevention through routine patrols, intelligence sharing, and coordination with the Navy, Customs, and BNN. However, enforcement remains constrained by limited personnel, only two patrol vessels, and the absence of an integrated maritime surveillance system. Inter-agency coordination is still fragmented due to overlapping authority and the lack of formal legal frameworks. Moreover, socio-economic vulnerabilities within coastal communities increase local involvement in smuggling networks. The study concludes that sustainable maritime security requires strengthening institutional synergy, enhancing technological capacity, and empowering communities as active partners in surveillance. A unified maritime governance framework is essential to transform Bintan from a vulnerable transit hub into a resilient maritime border zone for Indonesia’s narcotics control strategy.